2019
DOI: 10.1098/rsif.2018.0934
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cell migration via morphological changes in focal adhesions depends on shear stress in MYCN-amplified neuroblastoma cells

Abstract: Neuroblastoma is the most common solid tumour of childhood, and it metastasizes to distant organs. However, the mechanism of metastasis, which generally depends on the cell motility of the neuroblastoma, remains unclear. In many solid tumours, it has been reported that shear stress promotes metastasis. Here, we investigated the relationship between shear stress and cell motility in the MYCN-amplified human neuroblastoma cell line IMR32, using a microfluidic device. We confirmed that most of the cells migrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Cells formed a stable attachment to the PDMS and nanopillar surfaces over time, and thus the aspect ratio increased with time. However, there was more frequent cytoskeletal rearrangements in cells on nanopillars than in cells on flat PDMS surfaces, which corresponded to more rapid cell movements, as shown in Supplementary movie SV 1 (b) 42 . In addition, the aspect ratio for cells on the silicon oxide surface remained the smallest for 16 h. With FN coating, the protein layer facilitated cell spreading in multiple directions, leading to a more rounded cell shape.…”
Section: Resultsmentioning
confidence: 95%
“…Cells formed a stable attachment to the PDMS and nanopillar surfaces over time, and thus the aspect ratio increased with time. However, there was more frequent cytoskeletal rearrangements in cells on nanopillars than in cells on flat PDMS surfaces, which corresponded to more rapid cell movements, as shown in Supplementary movie SV 1 (b) 42 . In addition, the aspect ratio for cells on the silicon oxide surface remained the smallest for 16 h. With FN coating, the protein layer facilitated cell spreading in multiple directions, leading to a more rounded cell shape.…”
Section: Resultsmentioning
confidence: 95%
“…However, this observation was contradictory to a previous study indicating that LSS causes inhibition of the migration of bovine aortic endothelial cell as compared to static condition while HSS increases the speed of migration of these cells [ 52 ]. Similarly, reports have also indicated that HSS increases the migration speed and directional migration of neuroblastoma IMR32 cells via regulating the MYCN protein [ 53 ]. Thus, it seems that the effect of HSS on cell migration may be controversial and may be depends on cell types, cell origin and the level of SS applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells had a smaller aspect ratio but frequent cytoskeletal rearrangement compared to those on at PDMS surface, corresponding to more rapid cell movement, as shown in Supplementary movie SV1(b). 43 In addition, the aspect ratio for cells on titanium oxide surface was larger than those on silicon oxide surface.…”
Section: Cell Migration and Cell Morphology On Different Surfacesmentioning
confidence: 99%